Applications of complex wavelets to locate source of transient in power system / Noralizah Hamzah and Azah Mohamed - Hamzah, Noralizah; Mohamed, Azah (UiTM Press, 2009)
This paper provides solutions in locating the source of the transient based on complex wavelet energy. By using the complex wavelet transform, the transient power at the monitoring point is first calculated and the complex wavelet energy is obtained by integrating the transient power. Initially, there is no wavelet energy during steady-state condition, but during a transient condition, a wavelet energy is produced by the transient disturbance in power distribution systems. By examining the change in the wavelet energy between the steady state condition and during transient event, it is possible to locate the source of a transient disturbance. From the wavelet energy plot against time, a change in wavelet energy from an approximately zero to a negative value indicates that the transient source is from downstream or in front of the monitoring point. On the other hand, a change in wavelet energy from an approximately zero to a positive value indicates that the transient source is from upstream or behind the monitoring point. To verify the proposed complex wavelet method, simulations using the PSCAD/EMTDC software have been performed. Simulation results prove that complex wavelet energy is capable of locating accurately the source of transients in a power distribution system.